PENGARUH PENAMBAHAN KARAGINAN DENGAN LEVEL YANG BERBEDA TERHADAP KOMPOSISI KIMIA, KUALITAS FISIK, SENSORIS DAN MIKROSTRUKTUR SOSIS AYAM - Arif Ismanto; Deny Sumarna (Buletin Peternakan, 2016)
Various microfloras residing in the human colon are significantly affected by dietary fiber. Shortage of dietary fiber in the human daily consumption contributes to gastrointestinal metabolic and cardiovascular disease. One source of dietary fiber is a type of various seaweeds. This research was conducted to determine the effect of carrageenan addition on restructured meat products quality (chemical, physical, sensory and microstructure). There were four treatments in this experiment, (1) chicken sausages without carrageenan addition, (2) chicken sausage with 3% carrageenan addition , (3) chicken sausage with 6% carrageenan addition, and (4) chicken sausage with 9% carrageenan addition. The parameters observed were chemical composition (collagen, fat, water, protein), physical quality (pH, tenderness, water holding capacity (WHC), cooking loss), sensory properties (colour, textures, taste, flavor, acceptability) and microstructure. Chemical composition and physical qualities data were analyzed using Anova. The differences between means were analyzed using Least Significant Different (LSD). Sensory properties data were tested using Method of Successive Interval (MSI). The results showed that the addition of carrageenan at different levels significantly (P<0,05) affected water content and pH value. The addition of carrageenan at different levels also affected taste of chicken sausages. The addition of carrageenan at different levels had no effect on color, aroma, texture, tenderness, and acceptability. Microstructure analysis showed that addition of carragenan lead to the appearence of gel network. (Key words: Carrageenan, Chicken sausages, Chemical composition, Physical quality, Sensory quality, Miacrostructure)